PENERAPAN TINDAK PIDANA PERZINAHAN DALAM PERSPEKTIF HUKUM POSITIF INDONESIA: STUDI KASUS DUGAAN PERSELINGKUHAN DAN PERZINAHAN OLEH PRAJURIT TNI DENGAN WAKIL KETUA BK DPD RI DI KALIMANTAN TENGAH - Bayu Aji Pramana; Sudarto (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
This study analyzes the application of the crime of adultery in the perspective of positive Indonesian law, especially Article 284 of the Criminal Code (KUHP), by taking a case study of adultery and adultery involving an Indonesian National Army (TNI) soldier and Deputy Chairman of the Honorary Council (BK) of the Regional Representative Council of the Republic of Indonesia (DPD RI) in Central Kalimantan. This case is interesting to study because it involves two legal subjects with special status: a TNI soldier who is subject to the military justice system and a state official who has ethical and disciplinary implications. The type of research used by the author is a normative legal research method with a statutory and conceptual approach method. Then analyzed using qualitative data analysis techniques. Based on the results of the study, it can be seen that. Article 284 of the Criminal Code is an absolute complaint offense, so the role of the reporter (legal husband or wife) is the main determinant in the continuation of handling cases of alleged adultery. As a TNI soldier, SRR is subject to two legal systems at once: general criminal law (KUHP) and military law. The alleged crime of adultery not only has the potential to violate Article 284 of the Criminal Code, but can also be subject to sanctions based on Law Number 31 of 1997 concerning Military Justice and the Code of Ethics for TNI Soldiers.